What Gets Measured Gets Improved—Setting Standards and Accreditation for Quality Improvement for Diabetes Services in Australia. (July 2021) - Andrikopoulos, Sofianos; James, Steven; Wischer, Natalie
The purpose of this article is to illustrate that setting standards of care is the cornerstone for excellence in diabetes management. This is underpinned by 3 activities: a standards and accreditation process, an audit and benchmarking program and a linked quality improvement plan. While there are many examples of local auditing and quality improvement programs, there are very few that are at a national level. The National Association of Diabetes Centres (NADC) was formed by the Australian Diabetes Society and the Australian Diabetes Educators Association to set standards of diabetes care in Australia. A rigorous accreditation process was put in place to recognize primary, secondary, and tertiary level diabetes centers that meet these standards. The NADC accreditation process is underpinned by a quality improvement plan, which must be submitted for accreditation to be granted and is informed by the Australian National Diabetes Audit (ANDA). ANDA is conducted annually to gather information about treatments, complications, self-care practices and quality of life outcomes and provides a national as well as an individual report to the participating center that is used to benchmark against other like centers. The ANDA reports are important to inform national policy and advocacy for diabetes care and to also provide information for quality improvement purposes for the individual participating center. We believe that the NADC Standards and Accreditation can be an exemplar for other countries to adapt and adopt to standardize diabetes care at the highest level.